Feasibility, safety and long term outcomes of complex left main bifurcation treatment using the nano inverted t stenting: a multicentre registry. (14th October 2021) - Rigatelli, G; Zuin, M; Vassilev, D; Huy, D; Nguyen, V T; Nguyen, N; Ronco, F; Roncon, L
Abstract: Background: The role of double stenting techniques in distal bifurcation left main (LM) disease has gaining interest over the latest years. Purpose: We present the 3-year multicentre registry outcomes of dual stenting using ultra-thin strut stents and the Nano Inverted-T (NIT) technique in complex unprotected true LM bifurcation disease. Methods: We analysed the procedural and medical data of consecutive patients enrolled between 1st January 2014 and 1st December 2019 in a multicentre registry for complex LM bifurcation disease treated with the double stenting technique called NIT due contraindications and/or refusal to surgical treatment. Target lesion failure (TLF) was defined as the composite of cardiovascular death, target-vessel MI (TVMI) and clinically driven target lesion revascularization (TLR). Results: Among two hundred-ninety-five patients (138 males, mean age 70.3±12.8 years), post-operative success was achieved in 100% of cases. Contrast volume, procedural time, and radiation exposure were 139.2±23.4 ml, 15.3±4.9 min, and 1080±1034 cGy/m 2 (Figure), respectively. At a mean follow-up of 39.5±0.6 months TLF rate was 6.1% (n=18) while TLR and cardiovascular mortality rates were 3.0 (n=9) and 2.6% (n=8), respectively. Clinically driven angiographic follow-up was available in 26.4% of patients at a mean time from the procedure of 7.5±0.4 months. Clinically restenosis rate was 3.3%. Conclusions: Revascularization of complex LM bifurcation disease using the NIT double stenting technique resulted feasible and safe with a low incidence of TLF, excellent survival rate and no stent thrombosis. Figure 1.The NIT technique is based on the use of ultra-thin strut (≤80 micron) stents and double stenting starting with side branch stenting frst. The side branch stent is precisely positioned with one possibly only strut protruding into the main vessel which is balloon crushed before the implantation of the main branch stenting. The Proximal optimization technique (POT)–snuggle kissing–POT sequence is mandatory to ensure the coverage of the side branch ostium by both side branch and main branch stents. Snuggle kissing was performed placing the LCX balloon with the proximal marker at the middle rather than at the proximal marker of the LM-LAD balloon, in order to minimize the elliptical deformation of the LM stent. Funding Acknowledgement: Type of funding sources: None.